SYMBOLISM OF THE TABERNACLE IN THE COMPOSITION THREE STEPS OF HARMONY: A THEOLOGICAL SEMIOTIC AND CULTURAL STUDY - Klemens Siburian; Mauly Purba; Pulumun P Ginting; Vanesia Amelia Sebayang; Junita Batubara (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2026)
This article investigates the creative process and theological foundations of the musical composition Three Steps of Harmony, which is systematically constructed upon the symbolic tripartite structure of the Tabernacle of Moses in Pentecostal theology. Utilizing an artistic research approach—following Hawkins’ model of exploration, improvisation, and composition—integrated with Charles Sanders Peirce’s semiotic analysis, the study maps the spiritual journey from the Outer Court to the Most Holy Place onto fundamental musical elements: rhythm, melody, and harmony. The research addresses a gap in church music literature by moving beyond purely functional liturgical studies toward an analysis of music as an epistemic medium—a conceptual framework that organizes complex spiritual teachings. The composition is specifically situated within the cultural context of Pentecostal congregations in Medan, North Sumatra, where music is viewed as a "lived" cultural event rather than a static aesthetic object. In the first movement (Outer Court), rhythm—including the use of applause and the cajon—serves as an index of communal bodily participation and the raw energy of repentance. The second movement (Holy Place) utilizes modern aerophones such as the saxophoneand trumpet, reflecting the adaptation of popular culture into sacred spaces to facilitate spiritual dialogue through contemporary timbres. The final movement (Most Holy Place) uses harmonic density and piano registers to symbolize divine perfection and the reunification of the believer with God. Findings demonstrate that theological concepts can be systematically translated into musical forms through the "principle of threeness," utilizing triplets, intervals of a third (ters), and triads. Ultimately, the study concludes that Three Steps of Harmony functions as a dynamic tool for cultural communication, bridging ancient biblical ritual with the contemporary identity of modern believers. By aligning musical structure with theological logic, the work offers a robust model for contemporary sacred composition that is both theoretically sound and culturally resonant. Keywords: music composition, pentecostalism, semiotics, cultural studies.